Ser libres bajo el poder del rey. El republicanismo y constitucionalismo de Bartolomé de Las Casas - Quijano, Francisco (El Colegio de México, A.C., 2015)
This article explains the basis of the political thought of Bartolome de Las Casas, based on an analysis of the language and arguments he used while participating in the polemics of his time. Challenging the traditional historiography, which tends to question the presence of republican or constitutional traditions in the Hispanic world during the Early Modern period, this article shows that Las Casas, while seeking conditions that would allow freedom to coexist with the monarchy, made use of the traditional sources of his epoch to anticipate ideas such as the popular origin of power, the limitation of authority through the will of the people, the defense of the common good over the claims of special interest groups and freedom understood as non-dependence.